The Creating Guidelines of Learning Community Development for Bang Khanun Sub-District Administration Organization, Bang Kruai District, Nonthaburi - Chearnkaitpradab, Jirawut (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The objective of this research were to; 1) study the level of being a learning community of the Sub-district Administrative Organization. 2) study the relationship between management factors and environmental analysis Strategy in terms of practice factors of success with the condition of being a learning community. 3) study the relationship between factors influencing being a learning community. Learning, organization, personnel, and knowledge management technology with the condition of being a learning community and 4) to present guidelines for the development of a learning community. This research is mixed-method research using quantitative research. By collecting a sample of 400 people and qualitative research of 16 people. The research results show that; 1) The level of being a learning community by covering behavior was found that self-knowledge was at the highest level (mean=4.31, SD=0.55), and thought patterns were at a high level (mean=3.82, SD=1.31). At the highest level (mean=4.35, SD=0.48), team learning was at the highest level (mean=4.35, SD=0.46). System thinking was at a high level (mean=3.88, SD=0.85). 2) The relationship between management factors and environmental analysis Strategy in terms of practice factors of success with the condition of being a learning community. 3) It was found that the factors influencing the learning community in terms of knowledge management had a positive influence on the learning community condition. With statistical significance at the .01 level, in terms of self-knowledge (β=0.33), systematic thinking (β=0.29), team learning (β=0.26), self-knowledge (β=0.24) in terms of thought patterns (β=0.22). 4) Creating a learning community development approach for Bang Khanun Subdistrict Administrative Organization to become a learning community the development strategy should be formulated into a learning community that can be put into practice.